A comparative examination of factors that affect the credibility of health information on social media. Issue 1 (1st February 2019) - Kim, Heejun; Choi, Bogeum
ABSTRACT: The purpose of this research is to investigate factors affecting the perceived credibility of health information on social media and their varying effects on different platforms. We incorporated Elaboration Likelihood Model as a theoretical framework for our inductive content analysis. Then we conducted a correlation analysis and regression analyses to examine the relationship between the perceived credibility and identified factors. Our study discovered an extensive set of credibility factors and statistically significant effects made by platform‐specific factors.